Activation temperature and particle size of palm kernel shell vs. the surface properties of activated carbon - Lee, Chuan Li; Chin, Kit Ling; H’ng, Paik San; Hafizuddin, Mohd Sahfani; Khoo, Pui San (North Carolina State University, 2023)
Granular activated carbon (GAC) and powdered activated carbon (PAC) are the two most common forms of activated carbon with varying particle size range. The goal of this study was to analyze the key factors (particle size and activation temperature) affecting the surface characteristics of GAC and PAC derived from palm kernel shell (PKS). The surface morphology suggested that the pore network in PKS-PAC is more developed than that in PKS-GAC owing to the presence of a micropore structure when prepared at lower activation temperatures. This study also demonstrated that activation performed on different PKS particle size range influenced the mesopore domain of the activated carbon produced. The PKS-GAC was found to have more mesopores than PKS-PAC, which made it more reliable for dye adsorption in water treatment. Overall, this study demonstrated that applying different particle size range of PKS during the activation process can have a significant influence on the surface characteristics, thus having a direct impact on the application of activated carbon. An accurate particle size range will ensure that the most cost-effective activated carbon is selected to achieve the desired performance objectives.